The welfare effects of leaving the EU: a first ex-post assessment - Nicolò Tamberi (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2024)
I provide estimates of the ex-post welfare effects of the UK exit from the EU after one year. First, I estimate the increase in trade costs between the UK and the EU by looking at changes in trade flows between the UK and the EU and a set of comparator countries. Second, I estimate the trade elasticity exploiting the change in the UK MFN tariff accounting for the endogeneity of trade policy. I then feed the estimated trade cost increases and trade elasticities to a modern multi-sector general equilibrium trade model to compute the welfare effects. In the first year, the UK exit from the EU reduced real consumption by 1.1% for the UK and by 0.1% for the rest of the EU.
Keywords: 330